Uncovering the relation between environmental damage and the rate of rainfall received through a Life Cycle Assessment (LCA) study on potable water production in Malaysia. - Sharaai, Amir Hamzah; Mahmood, Noor Zalina; Sulaiman, Abdul Halim (InTech, 2012)
The world climate change is a phenomenon that is widely discussed in recent times. It causes a huge impact to the population of the world. Global warming causes the world's rainfall pattern to change including Malaysia. Today wet and dry season is very hard to be accurately predicted. Rainy season is getting more frequent and causing destruction to properties and halting economic growth of a nation. Evidence shows that climate change and global warming is caused by human's own lifestyle and activities. Man's savage way is the main caused for global climate change. Life Cycle Assessment (LCA) is a tool that could be used to assess a product or service from cradle-to-grave. This tool is capable of proving that every human invention has weaknesses and is threatening human life. In water treatment process, chemicals and electricity is needed. A sudden increase in water level in river caused by heavy rain resulted in higher usage of chemicals to treat water. Life Cycle Impact Assessment (LCIA) which uses ecoindicator 99 evaluation method to assess the chemicals and electricity, shows that the production of Polyaluminium chloride (PAC) causes damage to human health (respiratory inorganic) while electricity generation is fast depleting the natural resource of fossil fuel such as natural gas. These situation show that the irregular rate of rainfall resulted from the world's climate change not only affect human (eg. Inorganic respitory) but also indirectly causing destruction to the environment (depletion of natural gas) during the treatment of water. To overcome this problem the use of PAC as coagulant can be substituted with Alum. From the impact analysis, it is found that by replacing PAC with Alum, damage is reduced to more than 90% in damage to human health and ecosystem quality. This the same if electricity generation using natural gas is replaced with the combination of natural gas and renewable energy technologies such as solar panels and hydroelectric. Impact analysis also shows that there is 50% reduction in damage to resources when 50% natural gas and 50% renewable energy (solar panel and hydroelectric) without affecting human health and the environment.